2017
DOI: 10.1098/rspb.2017.1767
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific and interspecific variation in thermotolerance and photoacclimation in Symbiodinium dinoflagellates

Abstract: Light and temperature are major drivers in the ecology and biogeography of symbiotic dinoflagellates living in corals and other cnidarians. We examined variations in physiology among 11 strains comprising five species of clade A We grew cultures at 26°C (control) and 32°C (high temperature) over a duration of 18 days while measuring growth and photochemical efficiency ( / ). Responses to thermal stress ranged from susceptible to tolerant across species and strains. Most strains exhibited a decrease in cell den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 52 publications
6
72
0
Order By: Relevance
“…This brings critical attention to the importance of examining the response of Symbiodiniaceae holistically as the responses in culture may not be representative of in hospite endosymbionts. To date, the vast majority of transcriptomic assessments of Symbiodiniaceae within the context of thermal stress have been performed exclusively on free‐living cultures (Barshis et al, ; Baumgarten et al, ; Díaz‐Almeyda et al, ; Gierz et al, ; Levin et al, ; Levin, Suggett, Nitschke, van Oppen, & Steinberg, ; Liew, Li, Baumgarten, Voolstra, & Aranda, ; Xiang, Nelson, Rodriguez, Tolleter, & Grossman, ), and while they have been insightful, they may present not only a reduced, but also a biased transcriptional picture of the alterations that occur in Symbiodiniaceae in hospite. Only one other investigation directly compared gene expression in hospite to free‐living conditions (Rosic, Pernice, Dunn, Dove, & Hoegh‐Guldberg, ), but it focused on only two heat‐shock protein genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This brings critical attention to the importance of examining the response of Symbiodiniaceae holistically as the responses in culture may not be representative of in hospite endosymbionts. To date, the vast majority of transcriptomic assessments of Symbiodiniaceae within the context of thermal stress have been performed exclusively on free‐living cultures (Barshis et al, ; Baumgarten et al, ; Díaz‐Almeyda et al, ; Gierz et al, ; Levin et al, ; Levin, Suggett, Nitschke, van Oppen, & Steinberg, ; Liew, Li, Baumgarten, Voolstra, & Aranda, ; Xiang, Nelson, Rodriguez, Tolleter, & Grossman, ), and while they have been insightful, they may present not only a reduced, but also a biased transcriptional picture of the alterations that occur in Symbiodiniaceae in hospite. Only one other investigation directly compared gene expression in hospite to free‐living conditions (Rosic, Pernice, Dunn, Dove, & Hoegh‐Guldberg, ), but it focused on only two heat‐shock protein genes.…”
Section: Discussionmentioning
confidence: 99%
“…There is an existing body of work demonstrating that the shift of the dominant symbiont (shuffling) or acquisition of new species of symbionts (switching) from the environment enables holobionts, the coral host and its diverse assemblage of symbionts, to better withstand climate‐related increases in seawater temperatures (Baker, ; Berkelmans & Van Oppen, ; Jones, Berkelmans, van Oppen, Mieog, & Sinclair, ; Lewis, Neely, & Rodriguez‐Lanetty, ; Rowan, ; Stat, Carter, & Hoegh‐Guldberg, ). More recently, significant differences in heat tolerance have been reported both within a single Symbiodiniaceae genus (Díaz‐Almeyda et al, ) as well as between genera (Grégoire, Schmacka, Coffroth, & Karsten, ), revealing that different Symbiodiniaceae species have differing thermal optima and tolerances. A well‐studied case is Durusdinium trenchii (previously Symbiodinium trenchii [LaJeunesse et al, ]), an ITS2–D1a subtype within Clade D, that confers an increase in heat tolerance of 1–1.5°C to coral hosts (Berkelmans & Van Oppen, ; Rowan, ).…”
Section: Introductionmentioning
confidence: 99%
“…The family Symbiodiniaceae is taxonomically diverse and is comprised of over seven distinct genera (LaJeunesse et al, 2018) with substantial within-genus variation representing groups of related species (Coffroth & Santos, 2005;LaJeunesse et al, 2018). Though many studies have examined functional trait diversity among and within Symbiodiniaceae genera (Frade, Bongaerts, Winkelhagen, Tonk, & Bak, 2008;Grégoire, Schmacka, Coffroth, & Karsten, 2017;Hennige, Suggett, Warner, McDougall, & Smith, 2009;Iglesias-Prieto & Trench, 1994;Karim, Nakaema, & Hidaka, 2015;Krämer, Caamaño-Ricken, Ricther, & Bischof, 2012;McGinty, Pieczoonka, & Mydlarz, 2012;Oakley, Schmidt, & Hopkinson, 2014;Ramsby, Shirur, Iglesias-Prieto, & Goulet, 2014;Robison & Warner, 2006;Rodríguez-Romän & Iglesias-Prieto, 2005;Suggett et al, 2008;Takahashi, Whitney, & Badger, 2009), fewer studies have examined functional trait diversity among and within closely related species within the Symbiodiniaceae (Diaz-Almeyda et al, 2017;Goyen et al, 2017;Klueter, Trapani, Archer, McIlroy, & Coffroth, 2017;Suggett et al, 2015). Functional trait variation is correlated with phylogenetic relatedness in some cases, but not in others, highlighting the need to examine functional trait variation at lower taxonomic scales (Suggett, Warner, & Leggat, 2017).…”
mentioning
confidence: 99%
“…The subtypes of C present were not determined. Although considerable physiological variability exists within and among subtypes within clades (Díaz‐Almeyda et al ), the A‐ and C‐types found in A. cervicornis are generally considered to be thermally sensitive compared to D1a. (Howells et al ; Díaz‐Almeyda et al ).…”
Section: Resultsmentioning
confidence: 99%